Superacid-promoted synthesis of polychlorinated dibenzofurans. Issue 33 (17th August 2016) - Qarah, Ahmad; Gasonoo, Makafui; Do, Dat; Klumpp, Douglas A.
Graphical abstract: Highlights: A one step procedure has been developed for the synthesis of polychlorinated dibenzofurans. The chemistry involves a superacid-promoted condensation reaction of o -chloranil and arenes. An unusual carbocation cyclization is proposed for the conversion. Abstract: Polychlorinated dibenzofurans have been prepared in one step by the condensations of o -chloranil with arenes in triflic acid. A mechanism is proposed involving formation of a monoprotonated quinone (carboxonium ion), electrophilic attack at the arene, and cyclization of a carbocation intermediate. The chemistry is further examined by spectroscopic and theoretical studies.